การเปรียบเทียบประสิทธิผลของกรดไฮยาลูโรนิกชนิดฉีดเข้าข้อที่มีน้ำหนักโมเลกุลต่ำและสูงในผู้ป่วยโรคข้อเข่าเสื่อม - กมลวรรณ บงกชเพชร (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
Objective: To compare the effectiveness of Low molecular weight intra-articular hyaluronic acid (LMW IA-HA, 1.4 million Dalton) and High molecular weight intra-articular hyaluronic acid (HMW IA-HA, 6 million Dalton) in the treatment of individual patients with both knee osteoarthritis (OA). Methods: A prospective, randomized, single-blind clinical trial was conducted in patients with primary OA and radiographic changes of Kellgren & Lawrence stage II or III in both knees. Individual patients were given both drugs: each knee received only one drug by simple randomization. The LMW IA-HA was injected once a week for 5 consecutive weeks. The HMW IA-HA was injected to the contralateral knee once a week for 3 consecutive weeks, and a placebo (0.9% NSS) was injected once a week in weeks 4-5. The Outcome measures of effectiveness and adverse drug reactions (ADR) in each knee of individual patients were assessed separately. The primary outcome was measured by The Western Ontario and Mc Master University Osteoarthritis (WOMAC) Index. The secondary outcomes were measured as follows: (1) the patient s global assessment, (PGA) (2) the amount of rescue medication use per week and (3) the physician s global assessment (PhGA). The study was conducted for 17 weeks. Results: Thirty-two patients were enrolled in this study (each group of 32 knees received either LMW IA-HA or HMW IA-HA). At the end of study, total WOMAC scores were decreased in both LMW IA-HA and HMW IA-HA treated knees (p<0.001). When compared with the baseline, the total WOMAC scores of each group were significantly decreased from week 3 and throughout the study. However, there was no significant difference in total WOMAC score between the LMW IA-HA and HMW IA-HA treated knees (p=0.689). It was shown that both the PGA and PhGA in HMW IA-HA treated knees had a significantly lower score (p<0.001) and HMW IA-HA treated knees seem to need less analgesics. The most frequent ADR detected was transient pain at injection site and no serious ADR was found in this study. Conclusion: Both LMW and HMW IA-HA gave significant clinical improvement during the 17 weeks of the study. There was no significant difference in the primary outcome between both drugs in the left and right knee of individual patients